Thermodynamics of quasi-particles at finite chemical potential - Gardim, F. G. [UNESP]; Steffens, F. M. [UNESP] (Elsevier B.V., 2009)
We present in this work a generalization of the solution of Gorenstein and Yang to the inconsistency problem of thermodynamics for systems of quasi-particles whose masses depend on both the temperature and the chemical potential. We work out several solutions for an interacting system of quarks and gluons and show that there is only one type of solution that reproduce both perturbative and lattice QCD. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Quark-gluon plasma; Quasi-particle